2004
DOI: 10.1016/j.jacc.2004.01.045
|View full text |Cite
|
Sign up to set email alerts
|

Significant reduction in restenosis after the use of sirolimus-eluting stents in the treatment of chronic total occlusions

Abstract: The use of SESs in the treatment of chronic total coronary occlusions is associated with a reduction in the rate of major adverse cardiac events and restenosis compared with BMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(78 citation statements)
references
References 20 publications
6
70
0
2
Order By: Relevance
“…16,17 However, comparison between different DESs in CTO intervention has not been well established. Furthermore, the efficacy of the EES for the treatment of CTOs remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 However, comparison between different DESs in CTO intervention has not been well established. Furthermore, the efficacy of the EES for the treatment of CTOs remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Die Restenoserate lag selbst nach Einführung der Metall-Stents bei 30-50%, und v. a. die Reverschlussrate war mit bis zu 20% deutlich höher als bei nichtokklusiven Läsio-nen [33,34]. Mit Einsatz der DES wurde diese Rezidivrate signifikant gesenkt, was nicht nur verschiedene Register [35,36,37], sondern letztlich auch randomisierte Studien belegten ( [38,39,40]; . Abb.…”
Section: Medikamentefreisetzende Stents Bei Chronischen Koronarverschunclassified
“…Success rate for occlusions < 15 mm in length is 71% versus 58% for longer lesions [15]. Data on mid-and long-term outcome after successful CTO recanalization are summarized in Tables 1 (for percutaneous transluminal coronary angioplasty [PTCA] in the treatment of CTO), 2 (for utilizing BMS, as well as comparison of BMS vs. PTCA in the treatment of CTO) and 3 (for DES vs. BMS in the treatment of CTO) [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. The majority of studies reported greater mid-and long-term event-free survival in patients with successful CTO recanalization compared to unsuccessful CTO treatment [19-22, 27, 31, 32].…”
Section: Angioplasty Success In Chronic Total Occlusionsmentioning
confidence: 99%
“…Based on decrease in restenosis and reocclusion rates after stent placement following successful CTO opening [23,24,26], stent implantation became a standard intervention in a recanalized CTO. Recent studies have documented superiority of DES over BMS for the treatment of CTO with better mid-term angiographic and clinical results, both for sirolimus-and paclitaxel-eluting stents [33][34][35][36].…”
Section: Angioplasty Success In Chronic Total Occlusionsmentioning
confidence: 99%